LANGUAGE EDUCATION AS A PANACEA TO A VIRILE WEST AFRICA COOPERATION AND INTEGRATION - Iyanda, Rabi'u O. (Sokoto Educational Review, 2020)
Language is the major medium of communication among human beings. The complexity of human interaction in the modem world cannot go on without language. It is key to mental relationship and understanding, leading to promotion of peace, cooperation and nation building. It is the fulcrum o f a people’s culture and whatever affects it has direct impact on the people. This paper gives the unquantifiable number of languages and their advantages, x - rays the derivable benefits that await the nations that form the ECOWAS, highlight the various approaches through which they can suppress rancor and forge ahead at national and international level through the medium of language.